2014
DOI: 10.1111/eff.12133
|View full text |Cite
|
Sign up to set email alerts
|

Temperature–growth patterns of individually tagged anadromousArctic charrSalvelinus alpinusinUngava andLabrador,Canada

Abstract: Individual measurements of annual, or within‐season growth were determined from tag‐recaptured Arctic charr and examined in relation to summer sea surface temperatures and within‐season capture timing in the Ungava and Labrador regions of Eastern Canada. Differences between two years of growth (2010–2011) were significant for Ungava Bay Arctic charr, with growth being higher in the warmer year. Growth of Labrador Arctic charr did not vary significantly among years (1982–1985). Regional comparisons demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…The improved growth and associated better reproductive output potential resulting from migrating to a marine environment constitute the most likely reason for the maintenance of the anadromy tactic in salmonids despite the related mortality costs (Dodson et al ., 2013; Hendry et al ., 2004). Comparisons of migratory‐driven growth in Ungava Bay (Nunavik) and along the Labrador coast (Nunatsiavut) have noted a beneficial link between anadromy and nearshore marine productivity in charr (Murdoch et al ., 2015). The findings of this study, therefore, suggest that anadromy is sufficiently fitness‐rewarding under current environmental conditions to be nearly consistently maintained once adopted.…”
Section: Discussionmentioning
confidence: 99%
“…The improved growth and associated better reproductive output potential resulting from migrating to a marine environment constitute the most likely reason for the maintenance of the anadromy tactic in salmonids despite the related mortality costs (Dodson et al ., 2013; Hendry et al ., 2004). Comparisons of migratory‐driven growth in Ungava Bay (Nunavik) and along the Labrador coast (Nunatsiavut) have noted a beneficial link between anadromy and nearshore marine productivity in charr (Murdoch et al ., 2015). The findings of this study, therefore, suggest that anadromy is sufficiently fitness‐rewarding under current environmental conditions to be nearly consistently maintained once adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting responses of charr to climate change remains challenging. Northward expansion of key prey like capelin could provide an important food source for the low productivity coastal ecosystems found along the north coast of Labrador (Murdoch et al 2015). Comparisons of Ungava and Labrador showed that slightly elevated temperatures coupled with higher local productivity were associated with notably better growth of Ungava charr (Murdoch et al 2015).…”
Section: Nain Inshorementioning
confidence: 99%
“…Northward expansion of key prey like capelin could provide an important food source for the low productivity coastal ecosystems found along the north coast of Labrador (Murdoch et al 2015). Comparisons of Ungava and Labrador showed that slightly elevated temperatures coupled with higher local productivity were associated with notably better growth of Ungava charr (Murdoch et al 2015). Conversely, the concomitant ecosystem changes that facilitate the northward expansion of prey may have negative effects on charr.…”
Section: Nain Inshorementioning
confidence: 99%
See 1 more Smart Citation